Analisis Pedagogical Content Knowledge (PCK) Guru MIPA di SMA Negeri 11 Kota Jambi - Yohafrinal Yohafrinal; Damris M; Risnita Risnita (Universitas Jambi, 2015)
This research is descriptive qualitative research. the purpose of this research is to analyse the pedagogical content knowledge of science’s teachers SMA Negeri 11 Kota Jambi, by using purposive sampling technique consist of nine teachers, they are two chemistry teachers, three biology teachers, three mathematics teachers and one physic teacher ware taken as a research subject are categorized as experienced, teachers who are competent in their field base on their educational background. Data collection was conducted a questionnaires reseach instruments by using a Likert scale measurement, then followed by interviews to a mathematics teacher, a physic teacher, a biology teacher and a chemistry teacher which is reinforced by chech of documents and field observations. The result showed that teacher’s knowledge of pedagogical content knowledge still low, it can be seen from the seven aspects of PCK teachers only four aspects that can be mastered by the teacher, they are knowledge learning strategies, knowledge of the subject matter and education learning, knowledge of communication with learners and knowledge of assessment and evaluation. three of PCK teachers who still don’t understand yet are knowledge of learners and their characteristics, knowledge of curriculum development and knowledge of potential learners development.